2022
DOI: 10.13057/biodiv/d231002
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity profile of multidrug-resistant (MDR) Escherichia coli isolated from dairy cow's milk in Probolinggo, Indonesia

Abstract: Abstract. Widodo A, Lamid M, Effendi MH, Khairullah AR, Riwu KHP, Yustinasari LR, Kurniawan SC, Ansori ANM, Silaen OSM, Dameanti FNAEP. 2022. Antibiotic sensitivity profile of multidrug-resistant (MDR) Escherichia coli isolated from dairy cow's milk in Probolinggo, Indonesia. Biodiversitas 23: 4971-4976. The presence of resistant bacteria in animal products such as milk can be a new threat because it is directly related to the human food chain. Resistant Escherichia coli has been widely studied and detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…This research affirms that Multidrug resistance (MDR) and extended-spectrum betalactamase (ESBL) producing Escherichia coli can be found in several dairy farms in Probolinggo district, East Java, Indonesia. The results are similar to previous research, which identified MDR E. coli from dairy cow's milk (Widodo et al 2022), raw milk samples from the shelter (Anshariesta et al 2021) and ESBL-producing E. coli from fecal dairy cows sample in East Java, Indonesia (Putra et al 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This research affirms that Multidrug resistance (MDR) and extended-spectrum betalactamase (ESBL) producing Escherichia coli can be found in several dairy farms in Probolinggo district, East Java, Indonesia. The results are similar to previous research, which identified MDR E. coli from dairy cow's milk (Widodo et al 2022), raw milk samples from the shelter (Anshariesta et al 2021) and ESBL-producing E. coli from fecal dairy cows sample in East Java, Indonesia (Putra et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The use of broad-spectrum antibiotics, such as tetracycline and β-lactams is more common in cases of clinical mastitis in dairy cattle, because of their effective results. Tetracycline and aminoglycoside groups are the primary choice of antibiotics for respiratory and digestive system issues, followed by a combination of sulfonamide-trimethoprim medications that have a considerable impact on rumen microbial activity, and thirdgeneration cephalosporin antibiotics (Economou et al 2015;Widodo et al 2022). The percentage pattern of MDR E. coli isolates to several antibiotic agents can be caused by inappropriate antibiotic administration or excessive antibiotic administration in the treatment of infectious diseases in dairy cattle (Chowdhury et al 2021) and can also be caused by contamination from the environment and farmers during the milking process or livestock activities that allow transmission of E. coli with multidrug resistant characteristics can occur (Ahmedsham et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastitis can be split into two categories based on bacterial contamination: mastitis brought on by agents from within the quarter and mastitis brought on by environmental contamination agents (Cobirka et al 2020). Compared to subclinical mastitis produced by environmental disease agents, the incidence rate of disease caused by pathogens from inside the quarter is higher (Widodo et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Setting the distance between cows, placing pens far from the kitchen, isolating cows in separate pens, brooming manure, and regularly washing dairy cows prevent the spread of MDR bacteria in dairy farms (Pandit et al 2021). However, groups of dairy cows close to one another can result in MDR bacterial infections (Widodo et al 2022). Control of bacterial diseases requires surveillance and laboratory tests (Langley et al 2015).…”
Section: Discussionmentioning
confidence: 99%